The Linguistic Characteristics of Article Titles in Applied Linguistics Published in Accredited National Journals of Different Sinta Scores - Apriani, Noni; Arsyad, Safnil (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The journal article (henceforth JA) title is regarded as an advertisement to promote the content of the research article to potential readers. The authors must write and organize their titles to be attractive by paying attention to the syntactic features of titles. This research aims at investing the average length, syntactic features, and the differences of JA titles in Applied Linguistics at different Sinta scores. The method used in this research was a mixed-method with an exploratory sequential design. 120 JA titles were included as corpora of this research taken from six journals at different Sinta scores. The analyses of data were conducted following Cheng et al. (2012)’s framework on the syntactic features, while the analysis of the average length of JA titles by counting the parts of speech of the titles. The results show that the average length of JA titles was in the range of 10.5 to 13.55 words. Moreover, there are three types of syntactic features of JA titles found in this research, namely nominal structure, compound structure, and Verb-Ing phrases. Furthermore, all groups of journals in applied linguistics at different Sinta scores tended to have the same average length and syntactic features of JA titles. The findings of this research give useful significance for Indonesian authors in applied linguistics especially new or novice authors should learn and use the common syntactic features of JA titles when writing an article in English to be submitted to reputable international journals.